ANALISIS HUBUNGAN FASILITAS DAN LINGKUNGAN DENGAN KEPUASAN PASIEN DI PUSKESMAS BARANTI KABUPATEN SIDENRENG RAPPANG - Asmila; Devy Febrianti; Sunandar Said (Bina Generasi : Jurnal Kesehatan, 2025)
Community health centers play a central role in providing quality and equitable basic health services to the community. However, national data from 2019 shows that the level of patient satisfaction in Indonesia has only reached 42.8%, reflecting major challenges in improving the quality of services. This study highlights the condition of the Baranti Community Health Center in Sidenreng Rappang Regency which faces obstacles in terms of medical facilities and the service environment. Problems such as damaged facilities, limited service space, long waiting times, and lack of comfort in the waiting room are factors that influence patient satisfaction. The purpose of this study was to analyze the relationship between facilities and the environment with patient satisfaction. This study used a quantitative method with a descriptive analytical approach and a cross-sectional design, involving 96 respondents selected through simple random sampling. The results of the Chi-Square test showed a significant relationship between facilities and patient satisfaction (p = 0.002), but the variables of the social environment (p = 0.039) and physical environment (p = 0.055) did not show a significant relationship. This study contributes to efforts to improve the quality of health services at the primary level by emphasizing the importance of adequate facilities. From an Islamic perspective, providing the best service is a form of worship and trust, and reflects the value of ihsan in serving fellow human beings.